Model analysis on effect of temperature on the solubility of recycling of Polyethylene Terephthalate (PET) plastic. (November 2022) - Karim, Syed Shujaat; Farrukh, Sarah; Matsuura, Takeshi; Ahsan, Muhammad; Hussain, Arshad; Shakir, Sehar; Chuah, Lai Fatt; Hasan, Mudassir; Bokhari, Awais
Abstract: The massive increase in the use of PET plastic bottles has raised the challenge of accumulated waste plastics disposal and its related environmental concerns. Reusing this plastic waste through a solvent-based recycling process seems to be an eco-friendly solution for eliminating waste plastic and converting them into high quality products. The selection of solvent with its temperature requirement for the dissolution of polymeric materials is crucial in the solvent-based recycling process. Therefore, an innovative MATLAB program named HSPs-TPT was designed and constructed in this work to evaluate the dissolving power of solvents. Through this program, the solubility of the waste PET polymer was examined in thirteen (13) different solvents at different temperatures. As a results, the degree of waste PET polymer dissolution in the solvents was presented as the polymer-solvent solubility diagram, which provided the information about the relative energy difference (RED) change with the temperature rise. The program also provided the temperature range effective for the dissolution of PET by indicating the minimum and maximum solubility point for each solvent, which was further validated by the experimental data found in the literature. The proposed MATLAB program can numerically analyse the solubility of a polymer in different solvents in a short time for the recycling process and fabrication of different value-added plastic products such as polymer monoliths and membrane filters. Graphical abstract: Image 1 Highlights: The solubility of waste PET was examined in 13 solvents at different temperatures. A MATLAB program for temperature based solubility analysis has been developed. The RED changes with the temperature rise was studied for each solvent. The temperature range for the PET dissolution for each solvent was determined. The miscibility order at minima and maxima solubility points were discussed.